The Critical Period of Hybrid Maize Varieties Against Weeds - Sepe, Muslimin; Bulawan, Juniaty Arruan; Suhardi, S. (Agrotech Journal, 2023)
The corn crop cannot be separated from the presence of weeds as crop disturbers. The presence of weeds often causes a decrease in yield and seed quality in corn crops. The yield reduction depends on the type of weed, density, duration of competition, and allelopathic compounds released by weeds. This study aimed to determine the age of the critical period of competition of hybrid varieties of corn plants against weeds, as well as corn grain production due to competition with weeds. The research was conducted in a group randomized design consisting of seven weed control treatments based on corn planting age and repeated three times. Observation parameters consisted of plant height, number of leaves, cob length, cob weight, and cob circumference. The observation results were analyzed followed by Least Significant Different (LSD) at 0.05 percent level. The test results showed that the critical period of competition of corn plants against weeds occurred at the age of 20-45 days after planting. The highest average corn cob weight occurred in the weed control treatment in the third week after planting which was 126.67 gr. There was a compatibility between corn plants and weeds in the form of competition for nutrients and growing space, which affects production